Oral communication apprehension in English among Jordanian postgraduate students in Universiti Utara Malaysia - Mohammad Huwari, Ibrahim Fathi; Abd Aziz, Noor Hashima (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
This research investigated oral communication apprehension among the Jordanian postgraduate students studying in Universiti Utara Malaysia (UUM). It was directed by two main objectives: (1) to investigate the levels of Communication Apprehension among the Jordanian postgraduate students when communicating in English in UUM and (2) to investigate the relationship between programme, age and socioeconomic status and Communication Apprehension. The sampling of this study consisted of seventy Jordanian postgraduate students in UUM. The researcher used McCroskey‟s (1981) questionnaire, Personal Report of Communication Apprehension (PRCA-24) to measure communication apprehension levels in four different situations (groups, meetings, dyads and public speaking). The results of this study showed that the Jordanian postgraduate students had high levels of communication apprehension and there was a positive relationship between communication apprehension and age, programme, and socio-economic status.